The role of modern technology in preserving mbira music - Perminus Matiure; Richard Muranda (Cogent Arts & Humanities)
The article focuses on mbira music and the decline of traditional methods of preserving cultural legacies in the wake of modern technology. The research has an emic perspective since the writers are mbira players. The research is qualitative with face to face interviews in Gweru and Hwedza to collect data on mbira music and the role of technology on preservation. Findings indicate that recording, transcription of mbira pieces using software, formal teaching and performance contribute to the preservation of mbira music in Zimbabwe. Modern technology has positive and negative impacts, traditionalists blame modern technology for loss of originality and natural sonority of indigenous mbira music. Some participants are parochial of modern technology in preserving indigenous music. Dynamics of modern technology make some people uncomfortable hence their failure to appreciate and cope with the resultant changes. Mbira music is a beneficiary of modern ways of preserving traditional lore vulnerable to change.